Commitment, Competence, Leadership Style, and Work Culture on Job Satisfaction and Employee Performance at the Office of the Ministry of Religion, Kampar District - Ahmad Fadhli; Dadi Komardi; Rizaldi Putra (Journal of Applied Business and Technology, 2022)
This study aims to examine and analyze the effect of commitment, competence, leadership style, and work culture on job satisfaction and performance of employees of the Office of the Ministry of Religion, Kampar Regency. Data collection techniques are interviews, questionnaires, and employee data. The population in the study was 102 employees and the method used to determine the number of samples in this study was the total sample method using the census technique so the total sample was 102 respondents. Analysis using Structural Equation Modeling (SEM). The results showed that commitment has no effect on job satisfaction, competence has no effect on job satisfaction, leadership style has no effect on job satisfaction, work culture has an effect on job satisfaction, commitment has no effect on employee performance, competence has no effect on employee performance, leadership style has no effect on employee performance, work culture has no effect on employee performance and job satisfaction has no effect on employee performance.